(untitled) (Research, Society and Development, 2023)
Reconstructive surgery has gained importance due to the management of traumatic wounds, reconstruction after excision of neoplasms or aesthetic treatment. Correction techniques in reconstructive surgeries based on subdermal plexus flaps can be divided (advancement, rotation, transposition and interpolation) and are based on the local vasculature of the skin. The main indications for the rotation flap are the repair of eyelids, some portions of the skull and the ventral and lateral portions of the neck, and it is also feasible for the preparation of defects caused by the removal of small tumors on or near the eyelid or in the skull. The main postoperative complications of this technique are suture dehiscence due to excess tension at the edges of the wound and seroma. This work aims to report the use of reconstructive surgery using the subdermal rotation flap technique in a dog with a history of trauma to the skull region with contamination of the wound by myiasis and involvement of the eyeball.